2009
DOI: 10.1016/j.ijdevneu.2009.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diclofenac sodium administration increases the number of Purkinje cells in female rats: a stereological study

Abstract: Diclofenac sodium (DS) may affect the number of Purkinje cells in the developing cerebellum since DS can easily be transported from the maternal to the fetal physiological system during the pregnancy. In the present study, the effects of prenatal exposure to DS on the number of Purkinje cells in the cerebellum of 4-week-old (4W-old) and 20-week-old (20W-old) female rats were investigated. There were two main groups: the drug-treated group (DTG) and the control group (CG). Beginning from the 5th day after matin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…Similar results of the side effects of prenatal exposure to DS on the central and peripheral nervous tissues were also found by our group (4)(5)(6). On the other hand, even prenatal exposure of DS increased total Purkinje cell number in the female rats (37), but no significant differences were found between the granular cell numbers of male juvenile and adult rats exposed to DS prenatally (38). These results may be sex-dependent and require a detailed explanation.…”
Section: A B Csupporting
confidence: 86%
“…Similar results of the side effects of prenatal exposure to DS on the central and peripheral nervous tissues were also found by our group (4)(5)(6). On the other hand, even prenatal exposure of DS increased total Purkinje cell number in the female rats (37), but no significant differences were found between the granular cell numbers of male juvenile and adult rats exposed to DS prenatally (38). These results may be sex-dependent and require a detailed explanation.…”
Section: A B Csupporting
confidence: 86%
“…The preliminary study results were compared with those from the literature. Our scan of the literature revealed that a sampling fraction of 1/10 and sections of 26-40 µm in thickness had been used in similar studies (15)(16)(17)(18)(19)(20)(21)(22). The main study was thus performed on a 1/10 section sample on the basis of 30-µm-thick sections.…”
Section: Section Preparation and Stainingmentioning
confidence: 99%
“…After observing the vaginal plug produced by male vesicular and coagulating gland secretions on the next day, the animals were accepted as pregnant. Pregnant animals were kept in a standard plastic cage on sawdust bedding in an air-conditioned room (20°C), under a 12/12-h light/dark cycle and fed ad libitum (Odaci et al, 2010). After mating, DS (Voltaren, NOVARTIS, Istanbul, Turkey) in a dose of 1 mg/kg was injected daily intraperitoneally (i.p.)…”
Section: Animals and Experimental Proceduresmentioning
confidence: 99%